Post-operative brachial plexus neuropraxia: A less recognised complication of combined plastic and laparoscopic surgeries - Jimmy Thomas (Indian Journal of Plastic Surgery)
This presentation is to increase awareness of the potential for brachial plexus injury during prolonged combined plastic surgery procedures. A case of brachial plexus neuropraxia in a 26-year-old obese patient following a prolonged combined plastic surgery procedure was encountered. Nerve palsy due to faulty positioning on the operating table is commonly seen over the elbow and popliteal fossa. However, injury to the brachial plexus has been a recently reported phenomenon due to the increasing number of laparoscopic and robotic procedures. Brachial plexus injury needs to be recognised as a potential complication of prolonged combined plastic surgery. Preventive measures are discussed.